Vascular calcification on the risk of kidney stone: a meta-analysis. Issue 1 (31st December 2023) - Huang, Linxi; Hu, Junjie; Xue, Cheng; Ding, Jiarong; Guo, Zhiyong; Yu, Bing
Abstract: Background: The association between vascular calcification (VC) and kidney stone is still inconclusive. Therefore, we conducted a meta-analysis to estimate the risk of kidney stone disease in subjects with VC. Methods: To identify publications from related clinical studies, we performed a search on PubMed, Web of Science, Embase, and Cochrane Library databases from their inceptions until 1 September 2022. According to obvious heterogeneity, a random-effects model was used to calculate the odds ratios (ORs) and corresponding 95% confidence intervals (CIs). Subgroup analysis was conducted trying to dissect the effects of VC in different segments and population regions in predicting kidney stone risk. Results: Seven articles were included with a total number of 69, 135 patients, of which 10, 052 have vascular calcifications and 4728 have kidney stones. There was a significantly higher risk of kidney stone disease in participants with VC versus control (OR = 1.54, 95% CI: 1.13–2.10). Sensitivity analysis confirmed the stability of the results. VC can be separated into abdominal, coronary, carotid, and splenic aortic calcification while pooled analysis of abdominal aorta calcification did not indicate a significant higher kidney stone risk. An obvious higher risk of kidney stone was observed in Asian VC patients (OR = 1.68, 95% CI: 1.07–2.61). Conclusion: Combined evidence of observational studies suggested patients with VC may be associated with an increased risk of kidney stone disease. Despite the predictive value was relatively low, it is still worth noting that patients with VC are under the threat of kidney stone disease.